Crime Survey for England and Wales, 1996-2019/20 and 2022/23: Secure Access (Crime Survey for England and Wales, 2025)
The Crime Survey for England and Wales (CSEW), previously known as the British Crime Survey (BCS), has been in existence since 1981. The survey traditionally asks a sole randomly selected adult, in a random sample of households, details pertaining to any instances where they, or the household, has been a victim of a crime in the previous 12 months. These are recorded in the victim form data file (VF). A wide range of questions are then asked covering demographics and crime-related subjects such as attitudes to the police and the criminal justice system (CJS). Most of the questionnaire is completed in a face-to-face interview in the respondent's home; these variables are contained within the non-victim form (NVF) data file. Since 2009, the survey has been extended to children aged 10-15 years old; one resident of that age range has also been selected at random from the household and asked about incidents where they have been a victim of crime, and other related topics. The first set of children's data, covering January-December 2009, had experimental status, and is held separately under SN 6601. From 2009-2010, the children's data cover the same period as the adult data and are included with the main dataset. Further information may be found on the ONS Crime Survey for England and Wales web page and for the previous BCS, from the GOV.UK BCS Methodology web page. The main CSEW Secure Access dataset (SN 7280) includes: - the adult and child data also held in the standard End User Licence (EUL) version; adult self-completion modules on drinking behaviour, drug use, stolen goods, children's self-completion modules and sexual identity and low-level geography variables formerly held under Special Licence access conditions (please note that not all modules occur for each year - see the survey year's documentation for details); hate crime variables HATEMT3A-HATEMT3I and HATEPS3A-HATEPS3I from the Victim Form; the interpersonal violence (IPV) data (comprising the modules on domestic violence, sexual victimisation and stalking). For the 13th edition (August 2025), data and documentation for the 2022/23 CSEW were added to the study. No data available for 10-15 year-olds for 2022/23.